2016
DOI: 10.1021/acs.organomet.6b00079
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Hydrolysis of Uranyl, Neptunyl, and Plutonyl Gas-Phase Complexes Exhibiting Discrete Actinide–Carbon Bonds

Abstract: Gas-phase organoactinyl complexes possessing discrete An−C bonds (An = U, Np, Pu) were synthesized in a quadrupole ion trap by endothermic decarboxylation of [AnO 2 (O 2 C−R) 3 ]− anion complexes in which a formally AnO 2 2+ actinyl core is coordinated by three carboxylate ligands, with R = CH 3 (methyl), CH 3 CC (1-propynyl), C 6 H 5 (phenyl), C 6 F 5 (pentafluorophenyl). Decarboxylation and competing ligand loss were studied computationally by density functional theory complementing experiment. Although deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 66 publications
6
38
0
Order By: Relevance
“…The m/z 388 product is, therefore, generated by a dissociation reaction that involves elimination of acetyloxyl radical, CH 3 -at the MS/MS stage are consistent with earlier CID studies [26,30], including an investigation of decarboxylation and synthesis of organometallic actinide (An) species performed using a 3-D quadrupole ion trap [26]. …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The m/z 388 product is, therefore, generated by a dissociation reaction that involves elimination of acetyloxyl radical, CH 3 -at the MS/MS stage are consistent with earlier CID studies [26,30], including an investigation of decarboxylation and synthesis of organometallic actinide (An) species performed using a 3-D quadrupole ion trap [26]. …”
Section: Resultssupporting
confidence: 83%
“…More , had previously been prepared in a Bbottom-up^approach by insertion of U + into NO in an ion-molecule reaction [28], our experiments demonstrated that the species can also be created in a CID reaction. Formation of the nitrido species by transfer of N from cyanide was confirmed using precursors labeled with -in a 3-D quadrupole ion trap has been reported [26,30], and the structure of the species has been determined using infrared multiple-photon photodissociation (IRMPD) spectroscopy [31]. However, the experiments reported here demonstrate that the chemistry of product ions from both systems can be explored more accurately in the 2-D LIT.…”
Section: +mentioning
confidence: 78%
“…The IRMPD spectra were acquired using a QIT/MS similar to that previously employed to study uranyl-crown and organouranyl complexes. 39,40 The QIT/MS has been modified 41,42 such that the high-intensity tunable IR beam from FELIX can be directed onto the ion packet, resulting in multiphoton dissociation that is appreciable only when the IR frequency is resonant with a sufficiently intense absorption vibrational mode of the particular mass-selected complex being studied. The FEL produces ∼5 μs long IR pulses with an energy of ∼40 mJ/pulse at a repetition rate of 10 Hz.…”
mentioning
confidence: 99%
“…As an illustrative example, we consider the gas-phase organoactinyl complexes possessing discrete An -C bonds (An = U, Np, Pu) recently synthesized by Dau et al [57] in a quadrupole ion trap by endothermic decarboxylation of [AnO 2 (O 2 C -R) 3 ] -anion complexes. A formally AnO 2 2+ actinyl core is coordinated by three carboxylate ligands, with R= CH 3 (methyl), CH 3 CC (1-propynyl), C 6 H 5 (phenyl), C 6 F 5 (pentafluorophenyl).…”
mentioning
confidence: 99%
“…A formally AnO 2 2+ actinyl core is coordinated by three carboxylate ligands, with R= CH 3 (methyl), CH 3 CC (1-propynyl), C 6 H 5 (phenyl), C 6 F 5 (pentafluorophenyl). The chemical properties of these bonds were analysed by QTAIM [57]. Here, we calculate the partial atomic charges for the decarboxylation products, [(R)AnO 2 (O 2 C -R) 2 ] -with R = CH 3 and An=U.…”
mentioning
confidence: 99%